2020
DOI: 10.18421/tem92-33
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and Analyzing of Robotic Arm as Learning Media Based on Partial Least Square Method

Abstract: This research describes the use of a robotic arm on robot transporter as a learning media. Robot Transporter is a type of robot that can move and is equipped with a robotic arm. This robot is used to learn about the robotic arm concept which consists of the concept of arm and grip on the robot and the servo motor concept. The robotic arm concept is part of the electromechanical course at a private university in Indonesia. The purpose of this research is to analyse the relationship of the latent variables of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Studies related to learning media using robotics systems have been intensively researched by various scientists in the world. Buditjahjanto et al (2020) amalyzed the relationship of the latent variables of assembling, operating and evaluating with the latent variable of psychomotor skill on the arm robotic concept. They found that the latent variables, such as assembling, operating and evaluating, can make a significant contribution to students' psychomotor skills.…”
Section: Introductionmentioning
confidence: 99%
“…Studies related to learning media using robotics systems have been intensively researched by various scientists in the world. Buditjahjanto et al (2020) amalyzed the relationship of the latent variables of assembling, operating and evaluating with the latent variable of psychomotor skill on the arm robotic concept. They found that the latent variables, such as assembling, operating and evaluating, can make a significant contribution to students' psychomotor skills.…”
Section: Introductionmentioning
confidence: 99%